The Importance of Applied Behavior Analysis (ABA) Therapy in Nurturing Children with Autism Spectrum Disorder (ASD) According to Maqāṣid al-Sharī’ah - Zainal Abidin, Raihana; Alias, Muhammad Nazir; Wakhidah, Nur (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
This study evaluates applied behavior analysis (ABA) therapy for individuals with autism spectrum disorder (ASD) from the perspective of maqasid syariah, addressing the lack of research in this area. The research questions focus on how ABA therapy aligns with the principles of Maqāṣid al-Sharī’ah in ASD treatment. This qualitative study collected data from journal articles, reference books, and authoritative internet sources, which were thematically analyzed using an inductive approach. The findings indicate that ABA therapy plays a crucial role in helping individuals with ASD achieve the objectives of Maqāṣid al-Sharī’ah, including the preservation of religion, life, intellect, lineage/dignity, and property. ABA therapy was found to be effective in enhancing the ability of individuals with ASD to understand and practice religious teachings, reducing harmful behaviors, obtaining proper nutrition, improving cognitive function and mental health, addressing problematic sexual behaviors, and increasing work capacity and independence.